MASS MEDIA AS A SUBJECT OF PUBLIC CONTROL - Xurshida Hasanova (European Journal of Interdisciplinary Research and Development, 2023)
Social life itself demands that the mass media become an important and effective means of conveying the demands and needs of the population to the authorities, the closest helper and sympathizer of the people, and a mirror of democracy. Because mass media should critically and impartially assess the activities of authorities and management bodies, boldly raise shortcomings in various fields, and present problems. Citizens of the Republic of Uzbekistan, self-government bodies of citizens, non-governmental non-commercial organizations and mass media are considered subjects of public control. That is, subjects of public control supervise the activities of state bodies. In the formation of civil society, the cooperation of all institutions of civil society is of great importance. After all, the purpose of public control is to control how state authorities fulfill all their obligations to the population. The transparency of the activities of state administration bodies creates a convenient opportunity for public control. The article analyzes the activities of mass media as a subject of public control on a scientific basis.